Factors Affecting Staff Promotion of Small Medium Enterprises at Nanjing - Li, Yi Zhi (2014)
Talent has always been one of the most significant capitals to enterprise. The enterprise competition is actually talent competition. Meanwhile, as globalization intensifies, there is no denying that small and medium-sized enterprises have become increasingly important because they contribute a lot of GDP to their countries. Therefore, discussions surrounding the management of the SMEs have become a hot topic in recent years. Human resource managers need not only to solve the problem about talent shortage but also need to consider how to retain and motivate their employees in SMEs. Promotion is one method of motivating employees in organizations and but it is becomes a problem in terms of human resource management. Meanwhile, promotion can greatly kindle staff enthusiasm. Through promotion, employees can earn a higher salary, increased responsibility and authority as well as improve their social status. Promotion also provides a more senior position and a chance to meliorate their capabilities. But if the wrong people get promoted, this will cause speculation and doubts. While different companies have different promotion mechanisms, typically internal promotion is affected by employees’ educational background, experience, loyalty and interpersonal relationships. One continuing issue is how to improve the enterprise’s internal promotion mechanism. In addition, employees want to know which factor has the most direct impact on their promotion. The report will study promotion from the perspective of internal enterprise staff. Through literature review, this report will introduce four factors which influence internal staff promotion. Research methods will include quantitative methods and a questionnaire in practice. It is expected that this research could contribute to relevant enterprises to increase attention to internal staff promotion.